The Impact of Stimulation Induced Short-Term Synaptic Plasticity on Firing Patterns in the Globus Pallidus of the Rat - Bugaysen, Jenia; Bar‐Gad, Izhar; Korngreen, Alon (Frontiers in Systems Neuroscience, 2011)
Electrical stimulation in the globus pallidus (GP) leads to complex modulations of neuronal activity in the stimulated nucleus. Multiple in-vivo studies have demonstrated the modulation of both firing rates and patterns during and immediately following the GP stimulation. Previous in-vitro studies, together with computational studies, have suggested the involvement of short-term synaptic plasticity (STP) during the stimulation. The aim of the current study was to explore in-vitro the effects of STP on neuronal activity of GP neurons during local repetitive stimulation. We recorded synaptic potentials and assessed the modulations of spontaneous firing in a postsynaptic neuron in acute brain slices via a whole-cell pipette. Low-frequency repetitive stimulation locked the firing of the neuron to the stimulus. However, high-frequency repetitive stimulation in the GP generated a biphasic modulation of the firing frequency consisting of inhibitory and excitatory phases. Using blockers of synaptic transmission, we show that GABAergic synapses mediated the inhibitory and glutamatergic synapses the excitatory part of the response. Furthermore, we report that at high stimulation frequencies both types of synapses undergo short-term depression leading to a time dependent modulation of the neuronal firing. These findings indicate that STP modulates the dynamic responses of pallidal activity during electrical stimulation, and may contribute to a better understanding of the mechanism underlying deep brain stimulation (DBS) like protocols.